2006
DOI: 10.1002/mame.200600026
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Characterization of PP/Clay Nanocomposites Across the Length Scales of the Structural Architecture

Abstract: Summary: The structure and rheological properties of a large number of layered silicate poly(propylene) nanocomposites were studied with widely varying compositions. Morphology characterization at different length scales was achieved by SEM, TEM, and XRD. Rheological measurements supplied additional information about structure. The results showed that these materials possess a very complex structural architecture. The introduction of functionalized polymer decreased the size of the original clay particles and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 52 publications
(183 reference statements)
0
35
0
Order By: Relevance
“…This was expected as a result of the known weak interaction between organoclay and EVA with low VA content. It is, however, possible that minimal intercalation also occurred in the case of the 1% clay containing sample, because it has been shown that XRD is not a very reliable technique for establishing clay intercalation/exfoliation at low clay contents [13]. This observation is supported by the TEM image in Figure 2 that show the clay particles with little evidence of intercalation and no exfoliation.…”
Section: Resultsmentioning
confidence: 88%
“…This was expected as a result of the known weak interaction between organoclay and EVA with low VA content. It is, however, possible that minimal intercalation also occurred in the case of the 1% clay containing sample, because it has been shown that XRD is not a very reliable technique for establishing clay intercalation/exfoliation at low clay contents [13]. This observation is supported by the TEM image in Figure 2 that show the clay particles with little evidence of intercalation and no exfoliation.…”
Section: Resultsmentioning
confidence: 88%
“…Although the appearance of the silicate reflection in the XRD patterns proves the presence of tactoids and particles, it does not tell anything about their amount. In order to obtain a more quantitative estimate, the silicate peaks were integrated [24]. Integration was done in the Origin 8.5 software.…”
Section: Structurementioning
confidence: 99%
“…XRD is used to supply information on intercalation or exfoliation and the disappearance of the silicate reflection from the XRD pattern is falsely interpreted as a sign of complete exfoliation [19][20][21][22][23]. Usually subtle changes in gallery structure are not analyzed sufficiently thoroughly and reflection intensity indicating the amount of non-exfoliated silicates is not evaluated quantitatively practically at all [24]. Several studies clearly proved that the structure of layered silicate composites is complex [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations